Mechanisms of Resistance to ALK Inhibitors and Corresponding Treatment Strategies in Lung Cancer - Xie J; Gao Y; Xu W; Zhu J (International Journal of General Medicine)
Jiajun Xie,1,* Yinghao Gao,2,* Weiguo Xu,1 Jing Zhu1 1Department of Respiratory and Critical Care Medicine, Mian yang Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Mianyang, People’s Republic of China; 2Department of pulmonology, Mianyang hospital of T.C.M, Mianyang, People’s Republic of China*These authors have contributed equally to this workCorrespondence: Jing Zhu; Weiguo Xu, Department of Respiratory and Critical Care Medicine, Mian yang Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Mian yang, People’s Republic of China, Tel +86-0816-2243351, Email zhujing_1126@126.com; xwg522630@126.comAbstract: Lung cancer continues to be a leading cause of cancer-related mortality and morbidity worldwide. The echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) fusion gene accounts for approximately 3%-5% of gene mutation types. Targeted therapies for ALK mutations have made significant advancements in recent decades, enabling a considerable number of patients to achieve the goal of five-year survival benefits. However, overcoming the drug resistance that arises with current ALK tyrosine kinase inhibitors (TKIs) remain a major challenge in ALK-targeted therapies. In this review, we briefly discuss the primary and secondary mechanisms of resistance to ALK-TKIs, and explore treatment strategies based on progressive resistance models. Meanwhile, novel drugs and combination therapies are being actively researched and developed to address these challenges. The aim is to offer new insights into the mechanisms of resistance and the corresponding treatment strategies to ALK inhibitors.Keywords: EML4-ALK, ALK-TKIs, resistance mechanism, treatment strategies, lung cancer